Back end process yield improvement by verification of seeder bulk erase quality for 3.5" reowrk hard disk drive - Saidin, Mohamad Fadli (2014)
Hard disk drives (HDD) are key components of typical computers. One of the important processes in hard disk drive manufacturing is the servo track writing. Servo sectors are typically created and are not subsequently overwritten or erased. The process of writing servo sector patterns is known as Servo Track Writing (STW). During the STW process, interaction between the software command and hardware performance normally will cause several errors and imperfection in the process. Thus, this kind of failures required the media of the HOD to be erased to ensure no overlapping tracks or any signal/noise residue after it tested again as rework HDD. This research studies the process of erasing the servo signal in the rework hard disk drive using the bulk erase technology in Western Digital Malaysia. This project observed the current practice on how the defected servo signal written drives analysed and reworked using bulk erase method in the factory and also the status of current production yield, particularly in Tressels program. The focus of this project is to improve the yield of filler back end process by implementation of T AA profiling gating algorithm in the HDS seeder software at STW stations. Result of experiments tested and discussed with several statistical analysis tools such as ANOYA and T-Test to verify the yield improvement. With failed drives filtered from going to filler station using the enhanced algorithm in the HOS production software, yield improvement at back end process achieved around two percent.